1998
DOI: 10.4098/at.arch.98-9
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of licking the everted rectum in shrews (Soricidae, Insectivora)

Abstract: Haberl W. 1998. The behaviour of licking the everted rectum in shrews (Soricidae, Insectivora). Acta Theriologica: 43: 113-120.The behaviour of licking the everted rectum in shrews, hitherto referred to as "coprophagy" or "refection" is reviewed. To avoid confusion with "true" faeces-eating, it is proposed to persistently use the descriptive term "rectum-licking" when referring to this phenomenon. The behaviour is characterized by the animal everting the rectum by a series of abdominal contractions and licking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Shrews, small carnivores, have been observed to lick the everted rectum and this behaviour has been referred to as 'refection' or 'coprophagy'. However, it is not appropriate to refer to it as such because it has not been ascertained what was actually licked, which in most cases is probably not faeces (Hirakawa & Haberl, 1998). Haga (1960) reported that the Northern Pika (Ochotona hyperborea) has two types of faeces: one is a deep green, spherical, hard but friable faex which is defecated mostly during the daytime; the other is a blackish-coloured soft faex, coated with a gelatinous and viscous substance.…”
Section: Reingestion In Non-leporid Herbivoresmentioning
confidence: 99%
“…Shrews, small carnivores, have been observed to lick the everted rectum and this behaviour has been referred to as 'refection' or 'coprophagy'. However, it is not appropriate to refer to it as such because it has not been ascertained what was actually licked, which in most cases is probably not faeces (Hirakawa & Haberl, 1998). Haga (1960) reported that the Northern Pika (Ochotona hyperborea) has two types of faeces: one is a deep green, spherical, hard but friable faex which is defecated mostly during the daytime; the other is a blackish-coloured soft faex, coated with a gelatinous and viscous substance.…”
Section: Reingestion In Non-leporid Herbivoresmentioning
confidence: 99%
“…Whether the licking of the everted hindgut observed in many shrew species [e.g. 75] has a similar function remains to be investigated.
Figure 1Marker excretion patterns for a solute (liquid)-associated and a particulate marker in species with separation mechanism-based coprophagy and corresponding secondary marker excretion peaks (arrows) indicative of repeated marker ingestion via coprophagy.
…”
Section: Gastrointestinal Tract Evolution In Mammalsmentioning
confidence: 99%